1995
DOI: 10.1002/ecja.4410780703
|View full text |Cite
|
Sign up to set email alerts
|

Number of wavelengths required for constructing optical path network considering restoration

Abstract: Key words: Optical network; optical path; wavelength division multiplexing; failure restoration. 30ISSN8756-662 1 /95/0007-0030

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…The ratios of the number of wavelengths for a 15-node mesh network obtained by Nagatsu et al [40] are 15-20% with WT networks and about 40% with WNT networks. Simulation studies for a polygrid network have shown that the ratio decreases with the network size, largely due to increased wavelength reusability in different parts of the network as the number of nodes increases [41]. Studies for other networks such as the European optical network with 19 nodes, ARPANET with 20 nodes, and NSFNet with 14 nodes produced similar results [43], [47].…”
Section: Transport Network Restorationmentioning
confidence: 77%
See 1 more Smart Citation
“…The ratios of the number of wavelengths for a 15-node mesh network obtained by Nagatsu et al [40] are 15-20% with WT networks and about 40% with WNT networks. Simulation studies for a polygrid network have shown that the ratio decreases with the network size, largely due to increased wavelength reusability in different parts of the network as the number of nodes increases [41]. Studies for other networks such as the European optical network with 19 nodes, ARPANET with 20 nodes, and NSFNet with 14 nodes produced similar results [43], [47].…”
Section: Transport Network Restorationmentioning
confidence: 77%
“…These comparisons were made for centralized and preplanned restoration algorithms, and the number of wavelengths required for 100% protection against single-link failures with and without wavelength converters are computed [40], [41], [43], [47]. The heuristic WDM network design algorithms in these studies have been extended to design networks with excess resources for restoration.…”
Section: Transport Network Restorationmentioning
confidence: 99%
“…This is called the routing and wavelength assignment (RWA) problem [7], [8]. To solve the RWA problem, several heuristic algorithms were discussed [9]- [11]. In WP networks, the complex RWA should be solved since it requires wavelength continuity restriction, while it relaxes the complexity of OXC node structure [6], [7], [12] as it requires small size all optical switching systems.…”
Section: Path Networkmentioning
confidence: 99%
“…Point-to-point optical transmission evolved into optical routing using OXC/ROADM in the early 1990's [12]- [15], [85]. At that time the number of available WDM wavelengths per fiber was relatively small, [8][9][10][11][12][13][14][15][16], and hence PLC devices were utilized. Later, as available wavelengths per fiber increased, the PLC was replaced by WSSes based on 3-dimensional spatial optics.…”
Section: Future Directions On Optical Networkingmentioning
confidence: 99%
“…A majority of RWA studies are based on unrealistic assumptions about network-layer [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] on the one hand, such as unlimited capacity in each fiber, unlimited network equipment capacity and so on, and ignoring cost considerations on the other hand. In addition, paying no attention to the effects of transmission impairments on the signal quality, these studies assume that the physical-layer is an ideal one, permitting error free data signal transmission.…”
Section: Introductionmentioning
confidence: 99%